Large multinational evaluation of time to reintervention in patients undergoing bioprosthetic valve implantation during open heart surgery. (3rd October 2022) - Maller, T; Perel, N; Simonato, M; Harari, E; Tager, S; Fink, D; Jacobson, E; Glikson, M; Dvir, D
Abstract: Introduction: Bioprosthetic valves are increasingly utilized during open heart surgery in favor of mechanical valves. These tissue valves are prone for structural valve degeneration and failure, especially in young patients. Transcatheter aortic valve implantation (TAVI) is an appealing approach in these patients. Purpose: To describe independent correlates for early need for reintervention. Method: We used a large multicenter registry of patients (>45 years of age) with failed bioprosthetic surgical valves undergoing TAVI valve-in-valve (VinV) in either aortic or the mitral positions. Early reintervention was (<5 years between open-heart surgery and VinV). Multi-variable properties that were included: patient gender, age at open-heart surgery, valve size, baseline renal failure, position of valve implantation, and bioprosthetic valve label size. Results: A total of 3, 324 patients were included in the study (age at the time of open heart surgery 68.9+7.9 years). Median time to TAVI was 9 years (IQR 6–13 years). A total of 632 (19%) patients experienced early valve degeneration with median time to TAVI of only 3 years [IQR 1–5]. Patients with early degeneration were older than those without early degeneration (mean age at surgery was 72.8±9 years vs. 68.9±8 years; p<0.001). in addition, significant linear relation between older patient age and early valve degeneration (p for trend <0.001). Re-intervention in the mitral position was more common in the group of patients with early degeneration (24.4% vs 18.2% without early degeneration; p<0.001) Patient age and mitral valve position were independently associated with increased rate of early degeneration (OR 1.09 [1.08–1.11], p<0.001; OR 1.62 [1.31–2.01]; p<0.001 respectively). Conclusions: In this large multicenter analysis of patients undergoing TAVR for failed bioprosthetic valves we identified old patient age and mitral valve (vs. aortic) as independent correlates for early intervention. A discrepancy with known association of young age and rapid bioprosthetic valve degeneration is to be determined. Funding Acknowledgement: Type of funding sources: None.